การใช้ก๊าซไบโอมีเทนอัดกับหัวเผาก๊าซหุงต้มที่มีอยู่ในเตาเผาแบบชัตเติลในอุตสาหกรรมเซรามิก - วาฑิต พุทธปวน (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The objective of this work was to redesign rocket- and shower-type burners used in small scale ceramic kilns to allow the utilization of Compressed Biomethane Gas (CBG) as Liquefied Petroleum Gas (LPG) substitution. The mixing nozzle size was varied between 0.8 mm and 2.0 mm, the pressure range adjusted to 1-10 psi at different conditions of air inlet section area. (Physical flame) Data collection includes ignition characteristics, flame color and shape for comparison between CBG and LPG fuel. The optimal venturi size of rocket-type nozzle was 1.4 mm with 5 psi inlet pressure and 45% air inlet area. The optimal shower-type nozzle size was also 1.4 mm, pressure of 5 psi and the air inlet area set around 50% of normal operation. The test results in a ceramic kiln (0.1 m3) for rocket- and shower-type were found that using CBG replaces of LPG can be saved the cost about 27.92% and 29.73% respectively. The burner fuel consumption for the CBG of rocket- and shower-type venturi are measured to be 0.333 ± 0.003 kg/hr. and 0.330 ± 0.010 kg/hr. The thermal efficiency of the modified rocket- and shower-type CBG burners tested according to EN 203-2: 1995 standard are 55.76 ± 1.31% and 52.87 ± 1.20% respectively compared to 52.48 ± 0.16% and 53.48 ± 2.04% achieved from LPG burners.